Blood neurofilament light: a critical review of its application to neurologic disease - Barro, Christian; Chitnis, Tanuja; Weiner, Howard L. (Annals of clinical and translational neurology, 2020)
Neuronal injury is a universal event that occurs in disease processes that affect both the central and peripheral nervous systems. A blood biomarker linked to neuronal injury would provide a critical measure to understand and treat neurologic diseases. Neurofilament light chain (NfL), a cytoskeletal protein expressed only in neurons, has emerged as such a biomarker. With the ability to quantify neuronal damage in blood, NfL is being applied to a wide range of neurologic conditions to investigate and monitor disease including assessment of treatment efficacy. Blood NfL is not specific for one disease and its release can also be induced by physiological processes. Longitudinal studies in multiple sclerosis, traumatic brain injury, and stroke show accumulation of NfL over days followed by elevated levels over months. Therefore, it may be hard to determine with a single measurement when the peak of NfL is reached and when the levels are normalized. Nonetheless, measurement of blood NfL provides a new blood biomarker for neurologic diseases overcoming the invasiveness of CSF sampling that restricted NfL clinical application. In this review, we examine the use of blood NfL as a biologic test for neurologic disease.